2011
DOI: 10.1074/jbc.m111.231209
|View full text |Cite
|
Sign up to set email alerts
|

A Seeding Reaction Recapitulates Intracellular Formation of Sarkosyl-insoluble Transactivation Response Element (TAR) DNA-binding Protein-43 Inclusions

Abstract: The transactivation response element (TAR) DNA-binding protein-43 (TDP-43) is a nuclear protein that normally regulates transcription and splicing. Abnormal accumulation of insoluble inclusions containing TDP-43 has been recently reported in the affected tissues of amyotrophic lateral sclerosis (ALS) patients. Here, we show that intracellular aggregation of TDP-43 can be triggered by transduction of fibrillar aggregates prepared from in vitro functional TDP-43. Sarkosyl is found to be incapable of solubilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
242
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(252 citation statements)
references
References 36 publications
8
242
2
Order By: Relevance
“…6. In the presence of TDP-43, these polyubiquitinated proteins then could form the TDP-43(ϩ) UBIs with TDP-43 (57,58). To what extent and how generally applicable this proposed scenario is to the ALS cases with TDP-43(ϩ) proteinopathies awaits to be validated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…6. In the presence of TDP-43, these polyubiquitinated proteins then could form the TDP-43(ϩ) UBIs with TDP-43 (57,58). To what extent and how generally applicable this proposed scenario is to the ALS cases with TDP-43(ϩ) proteinopathies awaits to be validated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Saini et al (26) identified 246 -255 and 311-320 as core aggregation sequences of TDP-43 by evaluating the aggregation ability of a series of peptides derived from the TDP-43 C-terminal sequence (220 -414). Furukawa et al (27)reported that the C-terminal half of TDP-43 (i.e. TDP-432-C) can recapitulate the aggregation propensities of the full-length protein.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in VCP cause a multisystem proteinopathy consisting of motor neuron disease, frontotemporal dementia, inclusion body myopathy, and Paget's disease of bone [97], suggesting that impaired stress granule dynamics is a conserved thread in these disorders [10,96]. The formation of relatively stable, insoluble foci within the cytoplasm might accelerate self-aggregation of TDP43 and FUS via a prion-like mechanism [98], eventually leading to characteristic skein-like structures or large cytoplasmic inclusions typical of ALS pathology [6].…”
Section: Rna Granulesmentioning
confidence: 99%
“…Recombinant, aggregated TDP43 [98], and insoluble TDP43 isolated from the brains of patients with ALS or FTLD-TDP are capable of inducing TDP43 aggregation and cytotoxicity through a self-templated process in cultured cell lines [98,124]. Propagation of aggregated TDP43 and cell death could be inhibited by treating TDP43 extracts with formic acid, a powerful denaturant, but not by boiling or mild protease treatment, analogous to mammalian prions.…”
Section: Alternative Rna-based Mechanismsmentioning
confidence: 99%